Press tack needle stimulation for blunt chest trauma: a randomized double-blind control trial. (7th June 2022) - Kao, Pei-Yu; Lottering, Bernice; Lu, Ting-Yu; Ho, Wen-Chao; Lin, Yu-Sen; Huang, Tzu-Min; Chen, Chien-Kuang; Chen, Jian-Xun; Lee, Yu-Chen; Chen, Fang-Pey; Ben-Arie, Eyal
Abstract: OBJECTIVES: Blunt chest trauma is often associated with severe pain, reduced lung function and decreased sleep quality. This study aims to investigate the immediate and long-term effect of acupuncture on these factors using a randomized control double-blind design. METHODS: A total of 72 patients were randomized into 2 groups: treatment group (press tack acupuncture) and control group (press tack placebo). The face rating scale, numerical rating scale (NRS), portable incentive spirometer and Verran Snyder-Halpern sleep scale were measured at baseline, immediately after the intervention, and at the 4th day, with 2-weeks and 3-months follow-ups. RESULTS: There were no significant changes between the groups at the baseline measurements, with the exception of hypertension comorbidity. Immediately after the intervention and on the 4th day follow-up, the patients in the treatment group showed a significantly lower face rating scale when compared to the control ( P < 0.05). There were no significant changes in any of the other measurements between the groups ( P > 0.05). Subgroup analysis revealed that the NRS for turn over on the 4th day was reduced significantly in the treatment group of patients without lung contusion ( P < 0.05). For patients without pleural drainage, cough NRS in the treatment group was significantly reduced in the 2-week follow-up ( P < 0.05). CONCLUSIONS: This study showed that press tack acupuncture effects on pain reduction were inconclusive. However, future studies on the effect of acupuncture on blunt chest trauma patients are needed. Clinical trial registration: clinicaltirl.gov: NCT04318496. Abstract : Blunt chest trauma (BCT) is defined by a blunt injury to the rib cage, whereby the injury can vary in its severity from a local tissue injury to lethal injuries [1].